Membangun Repositori Institusi di Institut Agama Islam Negeri (IAIN) Kediri sebagai Pusat Deposit dan Pusat Literatur Ilmiah - Muhamad Hamim (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2019)
Gray literature is a collection published by universities in both printed and electronic formats, but not published for commercial purposes. Gray literature is currently mostly stored in printed form so it is vulnerable to damage. Therefore, in this study, we will discuss how to manage to serve this collection of gray literature. One way to deposit scientific work is by building institutional repositories. The aim of the institutional repository is to provide open access to scientific work produced by universities. In addition, institutional repositories can be used as indicators of college academic quality. With the increasing number of scientific works produced and published, the higher education institutions can be indicated as quality universities. The stages in building repository institutions include facility and infrastructure planning, system analysis and design, testing and repository implementation. The repository software that will be used is eprints with the main consideration is the number of users of this software in Indonesia. So that it is expected that when experiencing difficulties in its implementation, it can share with software users eprints. The advanced stage in building institutional repositories is the determination of upload regulations for scientific works and also the preparation of human resources that will manage repositories at IAIN Kediri.